Development and validation of an LC–MS/MS assay for the quantitation of a PEGylated anti-CD28 domain antibody in human serum: overcoming interference from antidrug antibodies and soluble target. (September 2014) - Gong, Chao; Zeng, Jianing; Akinsanya, Billy; Jiang, Hao; Mora, Johanna; Chilewski, Shannon; Gambardella, Janice; Allentoff, Alban; Gleason, Carol; Aubry, Anne-Francoise; DeSilva, Binodh S; Arnold, Mark E
Aim: To support drug development of a PEGylated anti-CD28 domain antibody, a sensitive and robust LC–MS/MS assay was developed for the first in-human multiple ascending dose study.Materials & methods: The procedure consists of a protein precipitation with acidified acetonitrile, followed by trypsin digestion of the supernatant. A surrogate peptide from the complementarity determining region was quantified with an LC–MS/MS assay using a stable isotope-labeled internal standard with flanking amino acids. An acid dissociation step was found to be essential to achieve full analyte recovery in the presence of antidrug antibodies and soluble target CD28.Results & conclusion: The fully validated LC–MS/MS assay demonstrates good accuracy (% deviation ≤6.3) and precision (%CV ≤5.2) with an lower limit of quantitation of 10 ng/ml.